Epidemiology of lameness in prepartum dairy heifers and its association with milk production, reproduction, and diseases in the postpartum period - B.S. Souza; R.R. Daros (Journal of Dairy Science, 2025)
ABSTRACT: Lameness directly affects the welfare and productivity of dairy cows, resulting in economic losses. However, little is known about lameness in prepartum dairy heifers. Here we investigated the development of lameness in 288 prepartum dairy heifers housed in freestall monitored from 10 to 20 mo of age. Data were collected on key transition period diseases (displaced abomasum [DA], retained placenta [RP], and metritis), milk yield during the first 100 d, and reproductive outcomes. Locomotion scores, hygiene scores, hock lesions scores, BCS, and behavior were collected monthly, until calving. Behavior was assessed using a one-zero sampling method, with 3 scans per visit. The air temperature in the freestall was recorded continuously during the study period. After calving, health and milk production data were collected from farm records. Data were analyzed in RStudio using mixed-effects linear and logistic regression models. Associations were measured both cross-sectionally and longitudinally. The incidence rate of lameness was 16 cases per 100 heifer-months. Over the entire study period, of 288 heifers, 172 experienced lameness at least once (59%), whereas 116 (41%) completed the study without any episodes of lameness. Cross-sectional analysis showed that dirtier limb scores and hock lesion scores were associated with increased odds of lameness. Heifers with a BCS ≤3 (1–5 scale) had higher odds of lameness and those lying down at the time of evaluation were 8 times more likely to be lame. From the longitudinal analysis, increased environmental temperature (42 to 70 d before the gait assessment) increased the likelihood of lameness. Heifers observed lame in all assessments before calving were 7 times (odds ratio: 6.8; 95% CI: 1.0–52.0) more likely to develop DA, RP, or metritis than heifers that did not present lameness in any assessment. Heifers that experienced lameness at least once before calving, regardless of recovery, had a lower hazard (hazard ratio: 0.61 95% CI: 0.40–0.96) of pregnancy. Milk production in the first 100 d was not affected by precalving lameness. In conclusion, the incidence of lameness during pregnancy of dairy heifers was high at the studied farm; factors previously associated with lameness in parous cows were also found to be associated with lameness in heifers.